Investor sentiment networks: mapping connectedness in DJIA stocks - Kingstone Nyakurukwa; Yudhvir Seetharam (Financial Innovation)
Abstract This study examines the connectedness of firm-level online investor sentiment using Dow Jones Industrial Average constituent stocks. Leveraging two proxies of online textual sentiment, namely news media and social media sentiment, we investigate sentiment connectedness at two levels: frequency interval and asymmetric level. Frequency connectedness dissects connectedness into short-, medium-, and long-term investing horizons, while asymmetric connectedness focuses on the transmission of positive and negative sentiment shocks on news and social media platforms. Our results reveal interesting patterns in which both news and social media sentiments demonstrate consistency in connectedness across the short-, medium-, and long-term. Regarding asymmetric connectedness, we observe that negative news sentiment has a higher connectedness than positive news sentiments.